Sosisalisasi Pembuatan Media Pembelajaran Berbasis Macromedia Flash kepada Siswa Kelas IX di Sekolah SMP Advent Kabanjahe - Ernawati Br Barus; Vera Charoline Br Barus; Harry Dito Meliala (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of computers in the teaching and learning process aims to improve the quality of teaching and learning. One of the competencies of teachers is applying information and communication technology in learning. Some problems that exist in society, especially in some schools, are the lack of multimedia-based learning materials in the classroom; learning using conventional methods; and the lack of use of information technology among teachers. Therefore, a workshop on how to create multimedia-based materials was proposed. The purpose of this workshop is to train teachers to build from scratch to multimedia-based teaching materials and train them to use information technology tools optimally. Some of the benefits requested are that teachers can learn new knowledge especially about multimedia; applications made by teachers can be used as initial applications to be used as one of the tools to transfer topics or subjects to their students. This workshop was held for one day from May 15, 2025 joining 20 educators from SMP Advent Kabanjahe. The result of this Socialization is the application of learning media teaching materials based on macromedia flash and can be used as one of the tools in the classroom to transfer knowledge to the class.